Black Swan in Phase Transfer Catalysis: Influence of Mixing Mode on the Stereoselectivity of Glycosylation; European Journal of Organic Chemistry; Vol. 2022, iss. 14 - Myachin I. V. Iljya; Mamirgova Z. Zarina; Stepanova E. V. Elena Vladimirovna; Zinin A. I. Aleksandr Ivanovich; Chizhov A. O. Aleksandr Olegovich; Kononov L. O. Leonid Olegovich (2022, 2022)
Title screen